The increasing instance of negative emotion reduce the performance of emotion recognition - Wang, Xiaomin; Zhao, Shaokai; Pei, Yu; Luo, Zhiguo; Xie, Liang; Yan, Ye; Yin, Erwei (Frontiers in Human Neuroscience, 2023)
Emotion recognition plays a crucial role in affective computing. Recent studies have demonstrated that the fuzzy boundaries among negative emotions make recognition difficult. However, to the best of our knowledge, no formal study has been conducted thus far to explore the effects of increased negative emotion categories on emotion recognition.With manual annotation and statistical evaluation, in the study, 29 video clips were selected as standardized elicitation samples to create a new material library of emotional film clips. A dataset of three sessions containing consistent nonnegative emotions and increased types of negative emotions was designed and built. The electroencephalogram (EEG) and the electrocardiogram (ECG) of 45 participants were recorded. The results revealed that as negative emotion categories increased, the recognition rates decreased by more than 9%. Further analysis depicted that the discriminative features gradually reduced with an increase in the negative emotion types, particularly in the θ, α, and β frequency bands. This study provided new insight into the balance of emotion-inducing stimuli materials.